Universiti Malaysia Sabah student nurses’ perceived readiness in caring for patients infected with coronavirus - Segaran Ramodran; Yeap, Boon Tat; Norkiah Saat; Liew, Constance Sat Lin; Nur Atikah Md Taib; Symeon Mandrinos (Malaysian Journal of Medicine and Health Sciences, 2020)
Recent Coronavirus outbreak has raised concern among student nurses who are doing their clinical posting tenure regarding the risk of patient acquired infection. This study examined perceived readiness to provide coronavirus patient care during clinical posting among student nurses in UMS. Method: This study deployed a cross-section survey design using a self-rated questionnaire to evaluate respondents’ level of readiness towards Coronavirus patient care. A total of 177 (N) respondents comprising of nursing students from UMS (year 1 n=55, year 2 n=56, year 3 n=66) participated in the study. The study questionnaire captured demographics and comprised of 15Likert -scale items that assessed the level of perceived readiness to provide Coronavirus patient care. The questionnaire was adapted from a previous SARs pandemic study and revalidated within the local context (α = 0.78). Data analysis used descriptive statistics by frequency counts and Fisher exact test for demographic correlates with the level of readiness. Results: Among 177 student nurses in this study68% (n= 121) were willing and ready to provide Coronavirus patient care and 32% (n = 56) were hesitant or not willing. Regarding confidence of safety using PPE to provide patient care, 34 % (n = 61) of respondents rated not confident and deemed it hazardous even with full PPE use. On the issue of if legally mandated to care for Coronavirus patients, 22% were hesitant to provide care and will consider leaving nursing training if compelled to do so. There was a significantly lower perceived level of readiness towards Coronavirus patient care among 1st-year student nurses and those who had not attended any Coronavirus educational session (p= 0.06). Conclusion: The findings indicate although the majority of student nurses are willing to provide care for Coronavirus infected patients during their clinical posting tenure, a small proportion of student’s nurses were hesitant.